The gargoyle - Davidson, Andrew; Hoppe, Lincoln, 1971- (Westminster, Md. : Books on Tape, 2008)
The narrator of this story is diving along a dark road when he is distracted by what seems to be a flight of arrows. He crashes into a ravine and suffers horrible burns over much of his body. As he recovers in a burn ward, undergoing the tortures of the damned, he awaits the day when he can leave the hospital and commit carefully planned suicide, for he is now a monster in appearance as well as in soul.
Unabridged.
Compact discs.
Read by Lincoln Hoppe.
Keywords: Burns and scalds -- Patients -- Fiction; Traffic accident victims -- Fiction; Hospital wards -- Fiction; Reincarnation -- Fiction; Stone carvers -- Fiction; Audiobooks; Books on CD; Psychological fiction; Historical fiction